( | 1 2 | x | + | 18 | ) | ( | 1 2 | x | − | 18 | ) | = | ( | 74 | ) | ( | 65 | ) |
Left side of the equation = | 1 2 | x | ( | 1 2 | x | − | 18 | ) | + | 18 | ( | 1 2 | x | − | 18 | ) |
= | 1 2 | x | × | 1 2 | x | − | 1 2 | x | × | 18 | + | 18 | ( | 1 2 | x | − | 18 | ) |
= | 1 4 | x | x | − | 9 | x | + | 18 | ( | 1 2 | x | − | 18 | ) |
= | 1 4 | x | x | − | 9 | x | + | 18 | × | 1 2 | x | − | 18 | × | 18 |
= | 1 4 | x | x | − | 9 | x | + | 9 | x | − | 324 |
= | 1 4 | x | x | − | 0 | x | − | 324 |
1 4 | x | x | − | 0 | x | − | 324 | = | ( | 74 | ) | ( | 65 | ) |
Right side of the equation = | 74 | ( | 65 | ) |
= | 74 | × | 65 |
= | 4810 |
1 4 | x | x | − | 324 | = | 4810 |